US Child Safety Seat Laws: Are they Effective, and Who Complies? - Lauren E. Jones; Nicolas Ziebarth (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2016)
This paper assesses the effectiveness of child safety seat laws. These laws progressively increased the mandatory age up to which children must be restrained in safety seats in cars. We use US Fatality Analysis Reporting System (FARS) data from 1978 to 2011 and rich state- time level variation in the implementation of these child safety seat laws for children of different ages. Increasing legal age thresholds is effective in increasing the actual age of child safety seat use. Across the child age distribution, restraint rates increase by about 30ppt in the long-run when the legal minimum age increases. However, we cannot reject the null hypothesis that restraining older children in safety seats does not reduce their likelihood to die in fatal accidents. We estimate that parents of 8.6M young children are "legal compliers." They compose an important target group for policymakers because these parents alter their parenting behavior when laws change.
Keywords: I18; K32; R41; 330; Child safety seats; age requirements; fatalities; FARS